2010
DOI: 10.1158/0008-5472.can-10-0522
|View full text |Cite
|
Sign up to set email alerts
|

The Sympathetic Nervous System Induces a Metastatic Switch in Primary Breast Cancer

Abstract: Metastasis to distant tissues is the chief driver of breast cancer-related mortality, but little is known about the systemic physiologic dynamics that regulate this process. To investigate the role of neuroendocrine activation in cancer progression, we used in vivo bioluminescence imaging to track the development of metastasis in an orthotopic mouse model of breast cancer. Stress-induced neuroendocrine activation had a negligible effect on growth of the primary tumor but induced a 30-fold increase in metastasi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
745
2
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 704 publications
(826 citation statements)
references
References 50 publications
31
745
2
10
Order By: Relevance
“…48,63 These results support the specific role of catecholamines and bARs in these effects of chronic stress on lung and skeletal metastasis and also suggest that activation of the HPA axis is not preponderant in this stimulatory effect, although it certainly does not exclude its contribution. In that regards, the stimulatory effect of high-dose glucocorticoids on b2AR expression in osteoblasts for instance suggests that SNS and HPA activation may synergize to favor skeletal metastasis of breast cancer cells.…”
Section: Stress B-blockers and Survival In Patients With Breast Cancermentioning
confidence: 56%
See 1 more Smart Citation
“…48,63 These results support the specific role of catecholamines and bARs in these effects of chronic stress on lung and skeletal metastasis and also suggest that activation of the HPA axis is not preponderant in this stimulatory effect, although it certainly does not exclude its contribution. In that regards, the stimulatory effect of high-dose glucocorticoids on b2AR expression in osteoblasts for instance suggests that SNS and HPA activation may synergize to favor skeletal metastasis of breast cancer cells.…”
Section: Stress B-blockers and Survival In Patients With Breast Cancermentioning
confidence: 56%
“…Studies related to breast cancer provided strong evidence for indirect effects of sympathetic cues on key host metastatic sites, including bones, lymph nodes and lungs, which are known to receive sympathetic innervation. A study by Sloan et al, 63 based on the use of 66cl4 breast cancer cells injected in the mammary fat pad of mice subjected to daily restrain or ISO injections, showed that sympathetic activation in mice stimulated the infiltration of activated macrophages (as well as myeloid-derived suppressor cells) into the parenchyma of the breast primary tumor and thereby induced a pro-metastatic gene expression signature that favors dissemination to distant organs. In vivo macrophage suppression, but not T-cell absence, inhibited metastasis of these cells to the lung under stress conditions, demonstrating the functional contribution of macrophages to this increase in lung metastasis.…”
Section: Chronic Stress Favors Ovarian Prostate and Breast Cancer Bomentioning
confidence: 99%
“…The neurotransmitters adrenaline and noradrenaline act as powerful regulators of numerous cellular and tissue functions and can promote tumor growth and metastases through the β-adrenergic receptors (β-AR), which are Gs-protein coupled receptors [152][153][154] . For instance, noradrenaline stimulates tumor progression in diverse types of malignancies activating β-AR which in turn induces the production of VEGF, interleukin-6 (IL-6) and matrix metalloproteinases [153,155] .…”
Section: Gpcrs Activated By Neurotransmittersmentioning
confidence: 99%
“…For instance, surgical stress induces the release of catecholamines that act on adrenergic receptors located in the membrane of cancer cells, thus stimulating their proliferation and invasiveness [33,34]. Opioids are the most commonly used analgesics in the perioperative period.…”
Section: Introductionmentioning
confidence: 99%